SURVEY OF NON-ALCOHOLIC FATTY LIVER DISEASE USING ULTRASOUND-GUIDED ATTENUATION PARAMETER (UGAP) IN ELDERLY PATIENTS WITH METABOLIC DISORDERS. (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate non-alcoholic fatty liver disease (NAFLD) in elderly patients with metabolic disorders using quantitative ultrasound assessment of hepatic steatosis (UGAP).Materials and Methods: A cross-sectional descriptive study was conducted on 168 patients aged ≥60 years with at least one metabolic disorder (diabetes mellitus, dyslipidemia, hypertension, or abdominal obesity [waist circumference ≥90 cm in men and ≥80 cm in women]) who attended National Geriatric Hospital from November 15, 2025 to December 30, 2025. Hepatic steatosis was assessed using the ultrasound-guided attenuation parameter (UGAP) technique on the LOGIQ Fortis (GE Healthcare). Results: The prevalence of NAFLD among the 168 elderly patients with metabolic disorders was 44.6%. Regression analysis showed that age and abdominal obesity were two factors associated with NAFLD. Abdominal obesity was associated with the severity of hepatic steatosis. Conclusion: Abdominal obesity is a predictor of NAFLD in elderly individuals. In contrast, diabetes mellitus, dyslipidemia, and hypertension were not associated with an increased risk of NAFLD in this population
Keywords: Fatty liver; NAFLD; quantitative ultrasound assessment of hepatic steatosis; UGAP; metabolic disorders; elderly.